Integrative literature review on human papillomavirus vaccination recommendations in national immunization programs in select areas in the Asia-Pacific region - Wanatpreeya Phongsamart; Pei-Jen Lou; Isaya Sukarom; Ying-Hui Wu; Omer Zaidi; Frieda Du; Alyssa Simon; Mark Bernauer (Taylor & Francis Group, 2024)
There is limited literature on current human papillomavirus (HPV) vaccination in the Asia-Pacific region. This integrative literature review was conducted to describe HPV vaccination programs in Hong Kong, Indonesia, Japan, South Korea, Malaysia, the Philippines, Singapore, Taiwan, Thailand, and Vietnam. Program descriptions, recommendations, f unding, and coverage data were extracted. Twenty-five citations were included. As of 2022, eight of the 10 areas of interest include HPV in their national immunization program (NIP) for school-aged girls; full implementation in Indonesia is expected in 2023 whereas Vietnam's NIP does not include HPV. Singapore also includes HPV vaccination for women (18-26 years). None of the HPV vaccination programs include males. In most areas (n = 7), programs include only one vaccine option. While female HPV NIPs are present in the Asia-Pacific region, opportunities remain to strengthen NIPs in broader populations (e.g., males, catch-up cohorts) to expand public health impact and provide gender equity in HPV vaccination.